KETAKUTAN TERHADAP KEMATIAN (Studi Komparatif Pada Manula Berdasarkan Kebiasaan Shalat Subuh Berjamaah di Masjid) - Mayrina Eka Prasetyo Budi (IAIN Ponorogo, 2018)
Abstract: Fear of death is experienced by most people, especially pensioners. This fear can be reduced by the feeling of Obedience to religion. The discipline for carrying out dawn prayer at the mosque can be used as a standard of faith and it can be an indicator for religious manner. The study aims to determine whether there is a different fear of death in elders based on the dawn prayer habits in at the mosque. The population of this comparative study was the elderly population at the age of 55 years or more who lives in densely populated villages and the distance of mosques and their houses is 1-500 meters. The instrument employed in this study was the Collett-Lester Original Fear of Death Scale. The result of validity and reliability degree was 92,995 and 0.627 respectively. The results showed that there was a difference in fear of death among seniors based on their dawn prayer habits in at the mosque. It can be seen from the result of ttest was 3.386 and higher than ttable, then Ho was rejected. Finally, it is recommended to rise worship as an effort to prepare provisions for facing death, one of them is by conducting dawn praying at the mosque.ملخص: يشعر معظم الناس بالخوف من الموت، خاصة كبار السن. يمكن لطاعة الدين أن تقلل من هذا الخوف. ويمكن استخدام صلاة الفجرجماعة فيالمسجد كمعيار للإيمان ودلالة على شخص أكثر دينية. وتهدف هذه الدراسة إلى معرفة ما إذا كانت هناك خلافات في الخوف من الموت في كبار السن على أساس عادات صلاة الفجرجماعة فيالمسجد. وهذا البحث مقارن، وكبار السن الذين يبلغون 55 سنة فما فوق ، مسلم ، يعيشون في قرى مكتظة بالسكان، ومسافة بينالمسجد والمنازل هي 1-500 متر، والصحة البدنية، ومستويات التعليم، قد تمالحج/ليس بعد، والناس العاديون/الشخصيات. صك The Collett-Lester Fear of Death Scale Original، محتويات التحقق 92،995، دقة 0.627. تحليل البيانات مع اختبار t، مستوى دلالة α = 0.05. وأظهرت النتائج أن هناك فرقا في الخوف من الموت في كبار السن على أساس عادات صلاةالفجرجماعة فيالمسجد، thitung=3.386 و Sig.t 0.001<0.05، ثم رفضHo.Mean1<Mean2، كبار السن الذين ليسوا مجتهدين لصلاة الجماعة في المسجد عند الفجر هم أكثر خوفا من الموت. يُنصح بزيادة العبادة كجهد لإعداد كنز لمواجهة الموت، أحدها بالصلاة عند طلوع الفجر في المسجد.Abstrak: Ketakutan terhadap kematian dialami sebagian besar orang, terutama manula. Ketaatan pada agama mampu mengurangi ketakutan tersebut. Kerajinan shalat subuh berjamaah di masjid dapat dijadikan standar keimanan dan indikasi seseorang lebih religius. Penelitian bertujuan mengetahui apakah ada perbedaan ketakutan terhadap kematian pada manula berdasarkan kebiasaan shalat subuh berjamaah di masjid. Jenis penelitian ini komparatif, populasi manula berusia 55 tahun ke atas, Islam, tinggal di perkampungan padat penduduk, jarak masjid dan rumah 1-500 m, sehat fisik, tingkat pendidikan bermacam-macam, status haji/belum, masyarakat biasa/tokoh. Instrument The Collett-Lester Fear of Death Scale Original, validasi isi 92,995, reliabilitas 0.627. Analisis data dengan uji t, taraf signifikansi α = 0,05. Hasil penelitian menunjukkan ada perbedaan ketakutan terhadap kematian pada manula berdasarkan kebiasaan shalat subuh berjamaah di masjid, thitung = 3,386 dan Sig.t 0,001 < 0,05, maka Ho ditolak. Mean1 <Mean2, manula yang tidak rajin shalat subuh berjamaah di masjid lebih takut terhadap kematian. Disarankan agar meningkatkan ibadah sebagai usaha mempersiapkan bekal menghadapi kematian, salah satunya dengan shalat subuh berjamaah di masjid.